Paradigms, Assumptions, Enclosure, and Violence: The Hillforts of Strathdon. Issue 2 (1st May 2013) - Cook, Murray
Abstract : This paper examines the assumptions and intellectual models that lie behind the debate around the connections between violence, warfare, and hillfort construction. These underlining academic paradigms have been heavily influenced by current social and political mores, which have created a context in which prehistoric and Early Medieval hillforts are studied in isolation and where the theoretical models have been developed from and with sole reference to the prehistoric period. In turn the debate in Scotland is based on a very limited number of dated hillforts. New excavation by the author from Aberdeenshire has allowed an attempt at an integrated settlement sequence and this is presented in the assumed context of violence as a dominant influencing factor in hillfort design and construction at specific periods.